2004
DOI: 10.1021/ja049644n
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Dependent Scope and Divergent Mechanistic Behavior in Nickel-Catalyzed Reductive Couplings of Aldehydes and Alkynes

Abstract: A new procedure for catalytic reductive coupling of aldehydes and alkynes has been developed. The procedure uses Ni(COD)2 with an imidazolium carbene ligand as the catalyst and triethylsilane as the reducing agent. A crossover deuterium-labeling experiment illustrated that variants involving trialkyl phosphines and imidazolium carbene ligands with a nickel catalyst proceed by different mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(39 citation statements)
references
References 25 publications
2
33
0
4
Order By: Relevance
“…[43][44][45] Auf diese ersten Arbeiten hin folgten bald intermolekulare Varianten der Nickel-katalysierten reduktiven Alkin-Carbonyl-Kupplungen. [37,46] Während nun stöchiometrische metallorganische Reagentien vermieden werden, sind andererseits terminale Reduktionsmittel wie Hydrosilane, Hydrostanna-ne, Organozinkreagentien, Organoborreagentien oder CrCl 2 nötig, die zu molaren ¾quivalenten von Nebenprodukten führen. Unter den Bedingungen der Rhodium-und Iridiumkatalysierten Hydrierung ist es dagegen möglich, reduktive Alkin-Carbonyl-und Imin-Carbonyl-Kupplungen mit hoher Regio-und Stereoselektivität ohne Bildung von Nebenprodukten durchzuführen (Schema 20).…”
Section: Methodsunclassified
“…[43][44][45] Auf diese ersten Arbeiten hin folgten bald intermolekulare Varianten der Nickel-katalysierten reduktiven Alkin-Carbonyl-Kupplungen. [37,46] Während nun stöchiometrische metallorganische Reagentien vermieden werden, sind andererseits terminale Reduktionsmittel wie Hydrosilane, Hydrostanna-ne, Organozinkreagentien, Organoborreagentien oder CrCl 2 nötig, die zu molaren ¾quivalenten von Nebenprodukten führen. Unter den Bedingungen der Rhodium-und Iridiumkatalysierten Hydrierung ist es dagegen möglich, reduktive Alkin-Carbonyl-und Imin-Carbonyl-Kupplungen mit hoher Regio-und Stereoselektivität ohne Bildung von Nebenprodukten durchzuführen (Schema 20).…”
Section: Methodsunclassified
“…Later, Montgomery showed that reductive couplings could also be accomplished using N -heterocyclic carbene (NHC) ligands with trialkylsilanes as reducing agents. 6 …”
Section: Reductive Coupling Reactions Of Alkynesmentioning
confidence: 99%
“…33 Recent applications in nickel-catalysed reductive coupling reactions have further illustrated the influence of the ligand on both reaction mechanism and regioselectivity. 34,35 Montgomery examined the macrocyclization of 28 and found that when R 1 is phenyl, both phosphine and NHC ligands afford product 30; however, when R 1 is methyl, different regioselectivities were observed (Scheme 5). 33 Use of triethylborane as the reducing agent and PMe 3 as the ligand favoured formation of endocyclic product 29 (9:2 ratio), whereas a combination of IPr and triethylsilane led to predominant formation of the exocyclic double bond (5:1).…”
Section: Effect Of N-heterocyclic Carbene Ligandsmentioning
confidence: 99%